2017
DOI: 10.1002/ejoc.201700803
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N‐Nitroso CHF2‐Pyrazolines and Their Transformation into CHF2‐Isoxazolines and ‐Pyrazoles

Abstract: N‐Nitroso CHF2‐pyrazolines were synthesized from in situ generated difluoromethyldiazomethane (CF2HCHN2), tert‐butyl isonitrite (tBuONO), and alkenes. The synthesis of representative CHF2‐pyrazoles and CHF2‐oxazolines was also performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Moreover, it is worth mentioning that only one equivalent of Ps-DFA was employed in these cycloaddition reactions. This is a distinct advantage compared with previously reported CF 2 HCHN 2 chemistry in which the diazo compound was often requisite for more than two equivalents. , …”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, it is worth mentioning that only one equivalent of Ps-DFA was employed in these cycloaddition reactions. This is a distinct advantage compared with previously reported CF 2 HCHN 2 chemistry in which the diazo compound was often requisite for more than two equivalents. , …”
mentioning
confidence: 88%
“…Despite considerable effort, these protocols often encounter formation of regioisomeric mixtures with respect to substituents incorporated at the 3- and 5-positions of the pyrazole ring. To overcome these limitations, Mykhailiuk reported the in situ generation of difluorodiazoethane (CF 2 HCHN 2 ) and its [3 + 2] cycloaddition with alkynes to provide 3-CF 2 H pyrazoles (Scheme a) . Subsequently, both the groups of Koenigs and Jamison have developed elegant methods to prepare CF 2 H-pyrazoles with CF 2 HCHN 2 by the utilization of continuous-flow technology (Scheme a) .…”
mentioning
confidence: 99%
“…For example, upon heating, they underwent eliminationo fn itrogen to form CHF 2 -isoxazolines 26 (Scheme 7). [30] Han, Chen, and co-workersf urther investigated this one-pot protocoli n[ 3 + +2]-cycloaddition reactions of CF 2 HCHN 2 (2)a nd 3-ylideneoxindoles to provide spirocyclic CHF 2 -substituted pyrazolines (27,28). The authors conducted this transformation in different solvents, and demonstrated the compatibility of the in situ preparation of CF 2 HCHN 2 with dichloromethane, chloroform, and acetonitrile.…”
Section: (A) Dipolar [3+ +2]-cycloaddition Reactionsmentioning
confidence: 99%
“…Substituted N ‐nitroso pyrazolines were shown to be valuable reactive heterocycles. For example, upon heating, they underwent elimination of nitrogen to form CHF 2 ‐isoxazolines 26 (Scheme ) …”
Section: Applications Of Cf2hchn2mentioning
confidence: 99%
“…Afterward, Koenigs and Jamison further investigated this transformation in a continuous-flow protocol. Except for alkynes, electron-withdrawing olefins could also be used as coupling partners to finish a [3 + 2] process with CF 2 HCHN 2 , affording the corresponding pyrazolines. ,, In 2016, Koenigs developed Rh­(II)-catalyzed one-step synthesis of difluoromethyl cyclopropanes from CF 2 HCHN 2 and aryl olefins in moderate yields . In our recent studies, we found that different kinds of CF 2 H-containing spirooxindoles and pyrazolo­[1,5- c ]­quinazolines could be easily synthesized from isatin-derived 3-ylideneoxindoles with in situ generated CF 2 HCHN 2 .…”
mentioning
confidence: 99%